2020
DOI: 10.17015/ejbe.2020.026.01
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the Regional Cooperation in Central Asia

Abstract: The purpose of the article is to study the regional cooperation of the countries of Central Asia (CA) among themselves and with other regions, as well as finding ways to improve it. The study revealed that regional cooperation is still at a low level. Significant trading partners of Central Asia are currently the EU, China, Russia, and Turkey. The participation of the countries of the region in the Eurasian Economic Union (EAEU) and the Chinese "Belt and Road" initiative (BRI) did not lead to the expected resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As regards to transforming Central Asia from a "land-locked``to a land-linked" region, Gussarova et al (2017) noted that the EEU and the Silk Road Economic Belt have been the most discussed undertakings. The same scholars compared the two major initiatives and two regional powers -Russia and China, with the EEU and the BRI, which directly influences the interests of Central Asia (Nurseiit 2020). Meanwhile, in their studies on the Silk Road and the service industries, Gursoy and Altinay (2021) concluded that the Silk Road project offers significant opportunities to develop an open-minded, all-encompassing, well-balanced, and inclusive regional economic cooperation framework that can benefit service industries and improve the quality of life of citizens of countries within the Silk Road.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As regards to transforming Central Asia from a "land-locked``to a land-linked" region, Gussarova et al (2017) noted that the EEU and the Silk Road Economic Belt have been the most discussed undertakings. The same scholars compared the two major initiatives and two regional powers -Russia and China, with the EEU and the BRI, which directly influences the interests of Central Asia (Nurseiit 2020). Meanwhile, in their studies on the Silk Road and the service industries, Gursoy and Altinay (2021) concluded that the Silk Road project offers significant opportunities to develop an open-minded, all-encompassing, well-balanced, and inclusive regional economic cooperation framework that can benefit service industries and improve the quality of life of citizens of countries within the Silk Road.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An overview of the Central Asian countries (multi-country) literature on the Granger causality (Granger, 1969) and VAR methodology (Sims, 1972) that plethora of survey around (Ashurov et al, 2020;Batsaikhan and Marek, 2017;Bird et al, 2020;Nurseiit, 2020;Rosenbaum et al, 2012). For example, Ashurov et al, (2020) investigated and identified the determinants of foreign direct investment (FDI) in the Central Asian countries, specifically Tajikistan, Kazakhstan, Kyrgyzstan, Turkmenistan, and Uzbekistan, between 2000 to 2017.…”
Section: Literature Reviewmentioning
confidence: 99%